‘It's something for you both to think about’: choice and decision making in nuchal translucency screening for Down's syndrome - Pilnick, Alison (Sociology of health & illness, 2008)
Policies and practices around antenatal screening services have long been the subject of debate in a sociological context. However, existing research has largely overlooked the way in which the policies and practices that underpin antenatal screening services are enacted through talk between pregnant women and their health professionals. This paper focuses on one such policy, that of informed choice. It uses data from 14 tape‐recorded pre‐screening consultations with community midwives, forming part of a newly introduced nuchal translucency screening programme, to examine how the issue of choice is topicalised and discussed. It concludes that, whilst there is clear evidence that midwives are at pains to explicitly invoke the issue of decision making, there are other more subtle factors in the interactional presentation of screening tests that serve to undermine whether and how a recognition of choice is received by pregnant women.